Supplementing growing rabbit diets with chestnut hydrolyzable tannins: Effect on meat quality and oxidative status, nutrient digestibilities, and content of tannin metabolites. (December 2018) - Dalle Zotte, Antonella; Cullere, Marco; Tasoniero, Giulia; Gerencsér, Zsolt; Szendrő, Zsolt; Novelli, Enrico; Matics, Zsolt
Abstract: The study investigated the effect of dietary inclusion of chestnut hydrolyzable tannin (CHT) in growing rabbit diets on nutrients digestibility, quality and oxidative status of meat, and content of tannin metabolites. At weaning, rabbits were assigned to 5 dietary groups ( n = 72 rabbits/diet): control medication-free (Co), control with coccidiostat (Cc), and T200, T400 and T600 (diets supplemented with 200, 400 and 600 g/100 kg CHT extract). Sixteen carcasses/treatment were considered and hindleg meat and Longissimus thoracis et lumborum (LTL) muscle were used for analyses. L*a*b* color values, water holding capacity, Warner Bratzler shear force, haem iron content, oxidative status and nutritional quality were unaffected by dietary treatments. Saturated fatty acids (SFA) and monounsaturated FA (MUFA) in LTL meat were higher in T600 than Cc rabbits ( P < .05), even though no differences were found for SFA and MUFA digestibility. Contrarily, polyunsaturated FA digestibility was lower in T400 and T600 than Co rabbits. No tannin metabolites traces were found in rabbit meat. Results of the present study showed that feeding CHT did not improve rabbit meat quality. Highlights: Rabbit meat quality did not benefit from the dietary inclusion of chestnut tannins. Dietary tannin supplementation did not improve rabbit meat oxidative status. Chestnut tannins in rabbit diets isn't a concern for rabbit meat consumption.